Pathophysiological Advantages of Spontaneous Ventilation - Lantos, Judit; Németh, Tibor; Barta, Zsanett; Szabó, Zsolt; Paróczai, Dóra; Varga, Endre; Hartmann, Petra (Frontiers in Surgery, 2022)
Surgical procedures cause stress, which can induce an inflammatory response and reduce immune function. Following video-assisted thoracoscopic surgery (VATS), non-intubated thoracic surgery (NITS) was developed to further reduce surgical stress in thoracic surgical procedures. This article reviews the pathophysiology of the NITS procedure and its potential for reducing the negative effects of mechanical one-lung ventilation (mOLV). In NITS with spontaneous ventilation, the negative side effects of mOLV are prevented or reduced, including volutrauma, biotrauma, systemic inflammatory immune responses, and compensatory anti-inflammatory immune responses. The pro-inflammatory and anti-inflammatory cytokines released from accumulated macrophages and neutrophils result in injury to the alveoli during mOLV. The inflammatory response is lower in NITS than in relaxed-surgery cases, causing a less-negative effect on immune function. The increase in leukocyte number and decrease in lymphocyte number are more moderate in NITS than in relaxed-surgery cases. The ventilation/perfusion match is better in spontaneous one-lung ventilation than in mOLV, resulting in better oxygenation and cardiac output. The direct effect of relaxant drugs on the acetylcholine receptors of macrophages can cause cytokine release, which is lower in NITS. The locoregional anesthesia in NITS is associated with a reduced cytokine release, contributing to a more physiological postoperative immune function.